Triangulation analysis for accommodation expenditure (Melaka UNESCO World Heritage Site) - Ab Rahman, Syakir Amir (2020)
A triangulation analysis output created by survey, interview and literature review in accommodation expenditure among domestic and inbound tourists, with the case study of Melaka UNESCO World Heritage Site.